Canadian Cannabis Industry and Social Responsibility: The Case of Canopy Growth - Aaraón Díaz Mendiburo (Norteamérica)
Through the ethnographic research developed primarily in the city of Smiths Falls, Ontario and desk review that included the consultation of digital platforms and the problematization of the concept of social responsibility, the objective is to reflect on the relationship between the corporate discourse of Canopy Growth and its social responsibility practices. The article is made up of different sections; first, it reflects on the incipient literature and its contradictions regarding cannabis through the lenses of various disciplines, as well as on the historical development of the concept of corporate social responsibility within capitalism, subsequently it identifies narratives regarding social responsibility promoted by Canopy Growth in its press releases and other digital inputs and some counter-narratives issued by other stakeholders. Finally, the narratives of members of the interest groups are presented, giving prominence to former Canopy Growth workers who, share their first-hand experiences in the corporation. The conclusions demonstrate the multiple inconsistencies that Canopy Growth embodies when raising the concept of social responsibility in its media discourses. These were evidenced by personnel who worked for the corporation in the city of Smiths Falls, Ontario. Knowing the modus operandi of a leading corporation in the cannabis industry gives us the tools that are necessary to envision its potential actions in Mexico given that Canopy Growth has shown an interest in expanding into our territory for several years.